Enhancing reading instruction through multimodal, literacy, and AI integration: A training program for high school English teachers - Sheila Agustina; Vidya Mandarani; Akbar Wiguna; Fika Megawati; Yunita Sabillah Damayanti; Achmad Oddy Syam Prayoga; Zaidan Al Zuhdi (CV. Yudhistt Fateeh, 2026)
Low levels of reading interest and student engagement remain major challenges in high school English instruction. This issue is further exacerbated by the continued use of conventional teaching strategies and the limited integration of multimodal media and digital technologies. This community service program aimed to enhance teachers’ pedagogical competence in teaching reading through a multimodal approach, literacy enrichment, and the use of Artificial Intelligence (AI). The program was implemented in three stages: a workshop, the development of teaching modules, and classroom implementation, involving 52 high school English teachers from the MGMP in Sidoarjo Regency. Data were collected through pre-activity and post-activity questionnaires and analyzed descriptively. The results indicate a significant improvement in teachers’ understanding of multimodal, literacy-based, and AI-assisted reading instruction, increasing from approximately 60–70% at the initial stage to over 85% after the workshop. All participants successfully developed instructional modules, and more than 75% implemented them in their classrooms. This implementation contributed to increased student engagement, as reflected in higher levels of participation and interaction during reading activities. These findings suggest that a practice-based training approach—integrating workshops, module development, and classroom implementation—is effective in enhancing teachers’ competence and promoting more interactive and contextualized reading instruction. It is recommended that similar programs be sustained through ongoing mentoring to ensure long-term impact.